2012
DOI: 10.2174/157340212800505007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mast Cell Chymase on Renal Disease Progression

Abstract: Chymase, a serine protease found in mast cell granules, is released into the interstitium following injury or inflammation. Chymase is the primary ACE-independent pathway of angiotensin II formation, and also functions to activate TGF-beta and other promoters of extracellular matrix degradation, thereby playing a role in tissue remodeling. In the diseased kidney, chymase-containing mast cells markedly increase and their density correlates with tubulointerstitial fibrosis severity. Studies in humans support the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 86 publications
(108 reference statements)
0
24
0
Order By: Relevance
“…However, alternative enzymes, such as cathepsins and chymases may produce functional AngII intracellularly (Kumar et al, 2008;Kumar and Boim, 2009). Depending on the cell type, cathepsin D can participate in the first step of intracellular AGT cleavage usually catalyzed by renin and the second step by chymase, not ACE (Wasse et al, 2012). Obviously, ACE inhibitors do not inhibit the intracellular RAS.…”
Section: Intracellular Renin-angiotensin System and Alternative Pamentioning
confidence: 99%
See 1 more Smart Citation
“…However, alternative enzymes, such as cathepsins and chymases may produce functional AngII intracellularly (Kumar et al, 2008;Kumar and Boim, 2009). Depending on the cell type, cathepsin D can participate in the first step of intracellular AGT cleavage usually catalyzed by renin and the second step by chymase, not ACE (Wasse et al, 2012). Obviously, ACE inhibitors do not inhibit the intracellular RAS.…”
Section: Intracellular Renin-angiotensin System and Alternative Pamentioning
confidence: 99%
“…These are intricate, highly efficient endogenous pathways in cardiac and smooth muscle cells, renal tubular, mesenchymal, as well as inflammatory cells infiltrating various tissues. Contribution of alternative pathways involving chymases, tonins, neutral endopeptidases, and aminopeptidases can significantly vary relative to classic RAS in a pathologic setting (Carey and Siragy, 2003;Chua et al, 2010;Wasse et al, 2012;Naffah-Mazzacoratti et al, 2014;Su, 2014).…”
Section: Intracellular Renin-angiotensin System and Alternative Pamentioning
confidence: 99%
“…Chymase has the ability to convert angiotensin I to angiotensin II, which regulates intrarenal blood flow, and also participates in renal interstitial fibrosis [11,12]. It is involved in renal remodeling by increasing the expression of transforming growth factor β (TGF-β) [13]. Tryptase is a serine protease expressed almost exclusively in mast cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mast cells actively participate in interstitial inflammation and contribute to renal fibrosis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of inflammation or injury, chymase is released into the interstitium and by activating latent transforming growth factor-b (TGF-b), is implicated in tissue remodeling. The number of mast cells correlates with the severity of tubulointerstitial disease: chymase-positive mast cells correlate with the severity of interstitial fibrosis and intra-renal vascular resistance [9]. Mast cell tryptase may also be involved in the development of interstitial fibrosis [10].…”
Section: Introductionmentioning
confidence: 99%